Focal postnatal deletion of Tsc2 causes epilepsy - McCoy, Carlie; Dusing, Mary; Jerow, Lilian G.; Winstel, Grace C.; Zhan, Felix; Rogers, Jason L.; Wesley, Madison; Otten, J. Brian; Danzer, Steve C.; LaSarge, Candi L. (Frontiers in Molecular Neuroscience, 2025)
IntroductionTuberous sclerosis complex (TSC) is a genetic disorder caused by mutations in either the TSC1 or TSC2 genes. These mutations prevent the TSC1/TSC2 protein complex from forming, resulting in hyperactivation of the mechanistic target of rapamycin (mTOR) cell growth and protein synthesis pathway. Epilepsy is one of the most common neurological symptoms in TSC patients, often associated with focal cortical lesions. However, it is not fully established whether such focal abnormalities are sufficient on their own to generate seizures and associated behavioral deficits. Here, we created a novel mouse model to test the hypothesis that a focal, postnatal deletion of Tsc2 from cortical neurons is sufficient to induce an epileptogenic network and produce behavioral changes relevant to TSC.MethodsTsc2 was deleted from neurons in a focal area of the frontal cortex in Tsc2fl/fl (fTSC2 KO) mice following neonatal bilateral AAV9-CaMKII-Cre-mCherry injections on postnatal day 2. One group of adult fTSC2 KO and Tsc2wt/wt (control) mice was implanted with cortical electrodes for combined video-EEG monitoring. A separate group of control and fTSC2 KO mice, injected with a lower viral titer, underwent video recording and behavioral exploration analysis in a novel environment. Tissue was collected for histology.ResultsAll adult fTSC2 KO mice implanted with cortical electrodes had seizures, whereas no control mice did. Histological analyses showed that virally infected cells in fTSC2 KO mice had enlarged somas and increased mTOR activation (pS6 expression). These fTSC2 KO mice also had decreased parvalbumin and somatostatin interneuron densities in the surrounding cortex. fTSC2 KO mice displayed increased anxiety-like behaviors, spending significantly less time in the center of the novel environment compared to controls.ConclusionA focal, postnatal deletion of Tsc2 from cortical neurons is sufficient to cause both epilepsy and behavioral deficits in mice. This model recapitulates key phenotypes of TSC, including abnormal cell growth, reduced inhibitory cell density, and increased microglia activation. This fTSC2 KO model is advantageous for delineating the cortical changes that support epilepsy and behavioral deficits in TSC, and for investigating possible targets for therapeutic intervention.